Cognitive [videorecording (DVD)] - Richards, Evan, 1970-; Fleischer, Rachel, 1980-; Brissey, Nina; Mambo, Ratidzo (Gravitas Ventures, 2025)
Alisha encounters a strange and mysterious couple forcing her to think she may not be who she thinks she is. A supernatural Hitchcockian thriller that keeps you guessing until the final frame.